Assessment of web searching behaviour of University of Ibadan distance learners (2020)
Purpose: The study was carried out to assess web searching behaviour of University of Ibadan distance learners Design/Methodology/Approach: Descriptive survey research design of the correlational type was adopted for the study. The population comprised 5200 distance undergraduates in three faculties; Education, Arts and Social Sciences. Stratified sampling technique was used to group the undergraduates into strata (100-500) Systematic random sampling technique was used to select every 10th elements of the population and the copies of questionnaire were randomly administered on them during class-contact hours at Sasa, Ibadan. Out of 520 copies of questionnaire distributed only 392 copies which constitute 75% return rate were found usable for the study; it was analyzed with the aid of frequency counts and percentages. Findings: The results revealed that the undergraduates of DLC use web-based information for academic and research activities. The findings further indicated that a significant number of respondents maintained negative web search strategies. Implication: Low bandwidth, poor ICT skills, poor ICT facilities and non-reliability of web-based information are some of the constraints that must be addressed while teaching web search strategies in Distance Learning programme of University of Ibadan. Originality/Value: The need to up-scale efforts at enlightens the learners on varying web-search strategies they could inculcate to enhance their learning and research capability was suggested. The paper will add to the body of knowledge in the area of information technology through web searching particularly among the distance learners in order to be in tune with global best practices.